Multimodal Simon Effect: A Multimodal Extension of the Diffusion Model for Conflict Tasks - Mahani, Mohammad-Ali Nikouei; Bausenhart, Karin Maria; Ahmadabadi, Majid Nili; Ulrich, Rolf (Frontiers in Human Neuroscience, 2019)
In conflict tasks, like the Simon task, it is usually investigated how task-irrelevant information affects the processing of task-relevant information. In the present experiments, we extended the Simon task to a multimodal setup, in which task-irrelevant information emerged from two sensory modalities. Specifically, in Experiment 1, participants responded to the identity of letters presented at a left, right, or central position with a left- or right-hand response. Additional tactile stimulation occurred on a left, right, or central position on the horizontal body plane. Response congruency of the visual and tactile stimulation was orthogonally varied. In Experiment 2, the tactile stimulation was replaced by auditory stimulation. In both experiments, the visual task-irrelevant information produced congruency effects such that responses were slower and less accurate in incongruent than incongruent conditions. Furthermore, in Experiment 1, such congruency effects, albeit smaller, were also observed for the tactile task-irrelevant stimulation. In Experiment 2, the auditory task-irrelevant stimulation produced the smallest effects. Specifically, the shortest reaction times emerged in the neutral condition, while incongruent and congruent conditions differed only numerically. This suggests that in the co-presence of multiple task-irrelevant information sources, location processing is more strongly determined by visual and tactile spatial information than by auditory spatial information. An extended version of the Diffusion Model for Conflict Tasks (DMC) was fitted to the results of both experiments. This Multimodal Diffusion Model for Conflict Tasks (MDMC), and a model variant involving faster processing in the Neutral-visual condition (FN-MDMC), provided reasonable fits for the observed data. These model fits support the notion that multimodal task-irrelevant information superimposes across sensory modalities and automatically affects the controlled processing of task-relevant information.